Dynamic Vision: Vision Therapy through the Anti-Gravity System. - Gates, Tanner (Journal of Behavioral Optometry, 2012)
In the four circle model, AM Skeffington proposed the idea of the anti-gravity system as one of the building blocks of vision. While the anti-gravity system is highly active in many vision therapy techniques, conditions can be arranged to ensure full engagement. This paper will briefly discuss the tecto-pulvinar pathway and vestibular system and explain how they play a role in vision therapy as it relates to the anti-gravity system. Specific vision therapy procedures emphasizing the anti-gravity system will be discussed.